JAMINAN SURETY BOND ATAS GRACE PERIOD DALAM PERJANJIAN SEWA GUNA ASET LEMBAGA MANAJEMEN ASET NEGARA - Amanda Aurelia (Fakultas Hukum Universitas Udayana, 2023)
The purpose of this article is to examine the importance of a guarantee against the risk of loss on the Grace Period policy or the postponement of lease payments provided by Lembaga Manajemen Aset Negara to their Collaboration Partners if there are Partners who cannot continue to charge rental rates when the Garce Period ends. The Grace Period itself is given a minimum of 3 (three) months for a 1 (one) year rental period and a maximum of 18 (eighteen) months for a 10 (ten) year rental period. Then, product guarantee is needed in this policy for the utilization of leased assets so that in the future LembagaAset Negara does not experience losses from this policy. This research is a normative juridical research, inwhich this study uses bibliographical data obtained by examining literary sources or mere secondary sources and interview techniques as a source of facts from research results to answer legal problems that occur. This research examines the surety bond guarantee as a product guarantee that can be provided by the Colaboration Partner as a commitment to fulfill the asset lease agreement contract for the Grace Period provided by Lembaga Manajemen Aset Negara. The results of this study indicate that surety bonds can be used as a product guarantee for the Grace Period Grace Period in the lease asset agreement managed by Lembaga Manajemen Aset Negara because it does not burden the partner's initial capital costs in carrying out its construction.